PENGUATAN KOMPETENSI GURU SMP DI KABUPATEN KEEROM MELALUI PELATIHAN DESAIN PEMBELAJARAN IPA INKLUSIF BERBASIS UNIVERSAL DESIGN FOR LEARNING (UDL) - C Tanta; St Rahmadani; Nurbaya Nurbaya; Suriyah Satar; Hanida LIstiani; Wiwin Olivia Febriyanty; Ratri Niken Estetika Putri (Jurnal Abdi Negeriku, 2026)
This community service program aimed to improve the competencies of junior high school science teachers in Keerom Regency, Papua Province in designing inclusive science learning based on Universal Design for Learning (UDL). The program was initiated due to the limited ability of teachers to develop learning practices that accommodate diverse student characteristics, the use of uniform teaching materials, and the low utilization of multi-format learning media and flexible assessments. The program was implemented through training and mentoring activities focused on developing inclusive science learning tools based on UDL principles for junior high school science teachers in Keerom Regency. The activities included program coordination, training on inclusive learning concepts and UDL principles, mentoring in the development of teaching modules and multi-format student worksheets, the creation of simple digital learning media, and program evaluation through pre-test and post-test assessments. The results showed an improvement in teachers’ pedagogical competencies and understanding of the UDL principles of engagement, representation, and action and expression in science learning. The program also produced inclusive science learning tools, simple digital learning media, and a community of practice for inclusive science teachers in Keerom Regency. This community service activity is expected to support the implementation of more adaptive, participatory, and inclusive science learning for students with diverse learning characteristics.